MANAGEMENT OF SOCIALISATION: A MICROECONOMIC APPROACH - Yurii Petrunia; Dmytro Maliar; Vira Petrunia; Nataliia Kovtun (Academy Review)
The aim of this study is to identify the objective factors of socialization, the driving forces behind individual decisions to achieve a certain level of socialization, the maximization of total utility from socialization, and the mechanisms for choosing the optimal amount of socialization and its self- management. The article examines leisure time, which can potentially be used for socialization, as the main factor in socialization. It is established that the allocation of time for social interaction directly depends on comparing the marginal utility of socialization with other activities, as socialization provides direct pleasure or utility. Based on marginal utility indicators, the mechanism of a person’s decision-making on increasing or decreasing social activity is determined. The article applies the cardinalist and ordinalist approaches to study human social equilibrium, a state in which maximum satisfaction of needs in communication or social relations is achieved. According to the cardinalist approach, the equimarginal principle of achieving the optimal level of social interactions is formulated. Under the ordinalist approach, it is shown that a person’s social equilibrium occurs when the marginal rate of replacement of other activities with socialization equals the ratio of the relative prices of socialization and other activities. The ordinalist approach is illustrated through a graphical model of human social equilibrium by combining the line of social limitation and the indifference curve in a single coordinate system. The article demonstrates that the decision on the optimal amount of socialization is directly influenced by the availability of free time for socialization and the time required for one social interaction. The presence or absence of free time essentially determines a person’s social limitation, or the availability of socialization as a benefit. Meanwhile, the relative cost of socialization (time per social interaction) determines how effectively available free time can be used for socialization. Thus, unlike human preferences, free time and the relative cost of socialization are objective factors of socialization. The article introduces for the first time concepts such as human social limitation, marginal utility of socialization, equilibrium level of socialization, marginal rate of replacement of other activities by socialization, and constructs the line of human ‘social limitation’, the line of human ‘social development’, the ‘time-socialization’ line, and the ‘price-socialization’ line. Additionally, a graphical model of the optimal level of human social interactions is presented, and types of digital pseudo- socialization are identified.